2017
DOI: 10.1007/s00213-017-4758-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effects of the kappa opioid receptor agonist nalfurafine on pain/itch-stimulated and pain/itch-depressed behaviors in male rats

Abstract: These results suggest that nalfurafine-induced decreases in pain/itch-stimulated behaviors may reflect nonselective decreases in motivated behavior rather than analgesia or antipruritus against the noxious and pruritic stimuli used here. This conclusion agrees with the absence of clinical data for nalfurafine analgesia and the weak clinical data for nalfurafine antipruritus. Nalfurafine bias for G protein signaling may not be sufficient for clinically safe and reliable analgesia or antipruritus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 57 publications
5
37
1
Order By: Relevance
“…uremic pruritus) resulted in biased ERK1/2 activation compared to p38MAPK induction in hKOPr-expressing HEK-293 cells and displayed antinociceptive effects in the tail immersion test (Schattauer et al, 2017) as well as in other species and preclinical pain models (Endoh et al, 2000); thus, further sustaining interest in developing KOPr agonists that result in limited p38MAPK phosphorylation (e.g., LOR17). However, it should be noted that nalfurafine was recently demonstrated not to be effective in relieving pain-depressed behaviors (Lazenka et al, 2018); consistently, nalfurafine is not indicated as analgesic drug not even in Japan (where it is marketed as an anti-itch drug). These limited effects displayed by nalfurafine may be related to a G protein signaling bias not high enough to produce a desirable profile of antinociceptive efficacy and safety (Lazenka et al, 2018); thus, pointing at the magnitude of bias factor as another element to be considered when developing new KOPr biased agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uremic pruritus) resulted in biased ERK1/2 activation compared to p38MAPK induction in hKOPr-expressing HEK-293 cells and displayed antinociceptive effects in the tail immersion test (Schattauer et al, 2017) as well as in other species and preclinical pain models (Endoh et al, 2000); thus, further sustaining interest in developing KOPr agonists that result in limited p38MAPK phosphorylation (e.g., LOR17). However, it should be noted that nalfurafine was recently demonstrated not to be effective in relieving pain-depressed behaviors (Lazenka et al, 2018); consistently, nalfurafine is not indicated as analgesic drug not even in Japan (where it is marketed as an anti-itch drug). These limited effects displayed by nalfurafine may be related to a G protein signaling bias not high enough to produce a desirable profile of antinociceptive efficacy and safety (Lazenka et al, 2018); thus, pointing at the magnitude of bias factor as another element to be considered when developing new KOPr biased agonists.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that nalfurafine was recently demonstrated not to be effective in relieving pain-depressed behaviors (Lazenka et al, 2018); consistently, nalfurafine is not indicated as analgesic drug not even in Japan (where it is marketed as an anti-itch drug). These limited effects displayed by nalfurafine may be related to a G protein signaling bias not high enough to produce a desirable profile of antinociceptive efficacy and safety (Lazenka et al, 2018); thus, pointing at the magnitude of bias factor as another element to be considered when developing new KOPr biased agonists. LOR17 displayed a bias factor of 853 as compared to U50,488, thus emerging as a candidate compound that is worthy of further characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is well consistent with many early studies in rodents with similar dose ranges of nalfurafine, but different from many “classic” KOP‐r agonists with several side effects. Specifically, low doses of nalfurafine (<40 μ g/kg) do not produce conditioned place aversion, sedation, anxiety‐like, or depression‐like behaviors (Inan et al., ; Liu et al., ; Nagase et al., ; Suzuki et al., ), though high doses (>80 μ g/kg) were reported to induce aversion (Lazenka et al., ). In humans, unlike other KOP‐r agonists, nalfurafine does not produce strong hallucinogenic or dysphoric effects (Kamimura et al., ; Kozono et al., ; Kumagai et al., , ; Pongcharoen and Fleischer, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while nalfurafine was shown to reduce acetic acid-induced writhing in mice (a pain-stimulated behavior), it did not restore ICSS thresholds depressed by acetic acid administration (a pain-suppressed behavior) (Lazenka et al, 2018). Furthermore, nalfurafine alone suppressed ICSS thresholds in the absence of a painful stimulus (Lazenka et al, 2018). These results seem to indicate that nalfurafine alone does not alleviate the negative affect produced by pain, unlike traditional opioid analgesics (Altarifi et al, 2014;Porreca and Navratilova, 2017b), and nalfurafine may prevent this positive effect of traditional opioid analgesics when co-administered.…”
Section: -Future Directionsmentioning
confidence: 98%
“…Other therapeutically limiting effects must also be investigated, such as constipation, a side effect of MOR agonists prevalent enough to prompt the development of naloxegol (a peripherally restricted MOR antagonist) and diuresis, a side effect of KOR agonism (Leander et al, 1985;Webster, 2015). In addition, while nalfurafine was shown to reduce acetic acid-induced writhing in mice (a pain-stimulated behavior), it did not restore ICSS thresholds depressed by acetic acid administration (a pain-suppressed behavior) (Lazenka et al, 2018). Furthermore, nalfurafine alone suppressed ICSS thresholds in the absence of a painful stimulus (Lazenka et al, 2018).…”
Section: -Future Directionsmentioning
confidence: 99%